The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/etc.3542
|View full text |Cite
|
Sign up to set email alerts
|

Exploring REACH as a potential data source for characterizing ecotoxicity in life cycle assessment

Abstract: Toxicity models in life cycle impact assessment (LCIA) currently only characterize a small fraction of marketed substances, mostly because of limitations in the underlying ecotoxicity data. One approach to improve the current data situation in LCIA is to identify new data sources, such as the European Registration, Evaluation, Authorisation, and Restriction of Chemicals (REACH) database. The present study explored REACH as a potential data source for LCIA based on matching reported ecotoxicity data for substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…For the algae, it could be argued that the EC50 determined at 72 h is a chronic endpoint (algal cells divide many times in 72 h), although from a regulatory point of view they are considered acute and NOEC or EC10 are considered chronic endpoints (EC‐JRC ). The use of duration limits to separate acute from chronic is consistent with a recent attempt to use REACH data to calculate USEtox substance hazard values (Müller et al ).…”
Section: Methodssupporting
confidence: 62%
“…For the algae, it could be argued that the EC50 determined at 72 h is a chronic endpoint (algal cells divide many times in 72 h), although from a regulatory point of view they are considered acute and NOEC or EC10 are considered chronic endpoints (EC‐JRC ). The use of duration limits to separate acute from chronic is consistent with a recent attempt to use REACH data to calculate USEtox substance hazard values (Müller et al ).…”
Section: Methodssupporting
confidence: 62%
“…For textile chemicals in products, as well as many other types of chemicals in products, there are no such strict regulations, which limit toxicity data availability. Müller et al (2017) explored the registration dossiers generated under the European REACH legislation as a data source for CFs. They found that REACH registration data can be used in USEtox but also highlight issues, such as differences in aim and scope between LCA and risk assessment methodology.…”
Section: Challenges and Possible Pitfallsmentioning
confidence: 99%
“…Several authors have indeed tested the usability of European data sources, e.g. Müller et al (2017), Saouter et al (2017a, b), and have concluded that the USEtox model and procedures need to be adapted to make it possible to use all available data, e.g. by allowing the use of chronic data expressed in other forms than EC 50 .…”
Section: Discussionmentioning
confidence: 99%